Intraoperative finding of Amyand’s hernia: case report and literature review (Basic Health sciencies journal, 2025)
The presence of the cecal appendix whether, inflamed, perforated, or intact, within the hernia sac is known as an Amyand hernia, a rare condition first described by surgeon Claudius Amyand in 1735 (with a global prevalence of 0.13%), which can mimic a strangulated hernia; This report describes the case of an elderly patient who underwent scheduled surgery for a right inguinal hernia, with a clinical history of two years. During the surgical procedure, a direct sliding inguinal hernia measuring 3 × 2 cm was identified. Upon opening the hernia sac, the cecal appendix was found in a phlegmonous phase, adhered to the sac wall. A decision was made to perform an appendectomy, the hernia sac was reintroduced, and the posterior wall of the inguinal canal was repaired using the Lichtenstein technique. As no complications occurred, the patient was discharged two days after surgery with outpatient antibiotic management.
Keywords: Amyand hernia; Lichtenstein technique; Phlegmonous appendix; Sliding hernia